ANALYSIS OF INTENSITY OF PAIN SYNDROME DURING THE FIRST WALKING IN PATIENTS AFTER TOTAL JOINT REPLACEMENT JOINTS OF LOWER EXTREMITIES - Koneva, E. S.; Serebryakov, A. B.; Kamalova, E. G.; Shapovalenko, T. V.; Tarbushkin, A. A.; Lyadov, K. V. (Travmatologii͡a︡ i ortopedii͡a︡ Rossii, 2012)
The aim of the study was to assess the severity of pain in patients after total replacement of joints of the lower extremities in the exercise of walking on the day of the surgery. Walking on the day of the operation was carried out for 46 patients the comparison group included 41 patients. As a result of the study, patients carrying walking on the day of operation, assessed the severity of pain in the 3.54+1.75 on a scale of pain NRS, and patients carrying walking on the next day after surgery 5.49+1.42 points. The results indicate not only the possibility of practical implementation of the function of walking on the day of operation, but also about the possibility of its implementation at a lower level of pain at the time of its implementationon the day of surgery.